2016
DOI: 10.1111/bjop.12194
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in visual attention: Implications for distraction processing

Abstract: We investigated differences between participants of East Asian and Western descent in attention to and implicit memory for irrelevant words which participants were instructed to ignore while completing a target task (a Stroop Task in Experiment 1 and a 1-back task on pictures in Experiment 2). Implicit memory was measured using two conceptual priming tasks (category generation in Experiment 1 and general knowledge in Experiment 2). Participants of East Asian descent showed reliable implicit memory for previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…Priming for each participant was calculated by subtracting the corresponding group average proportion of correctly answered baseline questions from the individual’s proportion of correctly answered target questions. This is typically done to account for random variation in individual baseline performance (e.g., differences in knowledge of baseline materials) and to control for individual differences in the opportunity to improve over the baseline and, thus, show priming effects (see Amer & Hasher, 2014; Amer et al, 2017; Rowe et al, 2006). The reactivation hypothesis was examined through planned comparisons between priming for reactivated and unreactivated words in the reactivation condition (within subjects) and between priming for both reactivated and unreactivated words in the reactivation condition and target distractor words in the control condition (between subjects).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Priming for each participant was calculated by subtracting the corresponding group average proportion of correctly answered baseline questions from the individual’s proportion of correctly answered target questions. This is typically done to account for random variation in individual baseline performance (e.g., differences in knowledge of baseline materials) and to control for individual differences in the opportunity to improve over the baseline and, thus, show priming effects (see Amer & Hasher, 2014; Amer et al, 2017; Rowe et al, 2006). The reactivation hypothesis was examined through planned comparisons between priming for reactivated and unreactivated words in the reactivation condition (within subjects) and between priming for both reactivated and unreactivated words in the reactivation condition and target distractor words in the control condition (between subjects).…”
Section: Resultsmentioning
confidence: 99%
“…Half of the participants were randomly assigned to the reactivation condition, and the other half were assigned to the control condition (see Table 1 for demographic information). To determine the sample sizes, we used averaged conceptual-priming effect sizes reported in previous studies using similar paradigms (Amer & Hasher, 2014; Amer, Ngo, & Hasher, 2017). On the basis of those studies, we calculated that a minimum of 29 participants was required to detect reliable (above baseline) conceptual-priming effects within groups ( d = 0.54), and a total sample size of 86 participants was required to detect priming differences between two groups ( d = 0.61), both with 80% power.…”
Section: Methodsmentioning
confidence: 99%
“…The Research Ethics Board at University of Toronto approved the study procedure and participants provided written consent prior to starting the experiment. All participants reported learning English before age 4 and did not identify as having an East Asian cultural background (see Amer, Ngo, & Hasher, 2016 for evidence of cultural effects on selective attention and subsequent memory). Demographic data for each group are presented in Table 1.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Their memory performance (corrected recognition scores for backgrounds and objects = .21 and .47, respectively) was about the same as that of the full Chinese sample reported in the present study who viewed the pictures with green objects (corrected recognition scores for backgrounds and objects = .18 and .48, respectively). In addition, Amer, Ngo, and Hasher (2016) found that even when East Asian participants were explicitly instructed to only pay attention to and work with focal information (e.g., pictures), and to ignore distracting information presented on the same screen (e.g., words), they still showed learning of the to-be-ignored information in subsequent tasks. Western participants, on the contrary, were able to just focus on the focal information and ignore the distracters; as a result, they were less likely than East Asians to show memory for the distracting information.…”
Section: Discussionmentioning
confidence: 99%